2023
DOI: 10.1186/s12905-023-02468-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of online solution-focused counseling on the sexual quality of life of women with a history of breast cancer: a clinical trial

Abstract: Background Breast cancer, as the most prevalent malignancy among women globally and in Iran, affects important aspects of the lives of the survivors of this condition, especially the quality of sexual life. Solution-focused brief therapy is one of the therapeutic counseling approaches used in various fields, including sexual function problems. In recent years, online and internet-mediated counseling methods have received more attention. Objective T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In total, seven studies reported a statistically significant improvement over time in overall quality of life [ 38 , 42 , 51 , 54 , 56 , 57 , 66 ]. Of these, three studies based their intervention on PLISSIT, which was applied to individual patients [ 38 , 54 , 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…In total, seven studies reported a statistically significant improvement over time in overall quality of life [ 38 , 42 , 51 , 54 , 56 , 57 , 66 ]. Of these, three studies based their intervention on PLISSIT, which was applied to individual patients [ 38 , 54 , 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…20,21 In the medical setting, SFBT is a good practice for patients' health-related psychosocial, behavioral, and functional health outcomes and medication adherence. 22 To our knowledge, there is no research on the use of SFBT for medication adherence interventions, and the SFBT used in the medical setting is usually a classic SFBT delivered by professionals, 23,24 which still sounds complex to general medical providers. The classic SFBT typically involves four to six sessions with three characteristic frameworks and more than ten representative questions with different uses and outcomes.…”
Section: Introductionmentioning
confidence: 99%